Pedagogical museology, context and citizenship - José María HERNÁNDEZ DÍAZ (Ediciones Universidad de Salamanca, 2017)
In this paper, we ask ourselves about the social sense of the museum dedicated to education, about the many pedagogical museums that have appeared among us in the last decades, with more and less fortune. A pedagogical museum should play a role in supporting the researcher in the history of education, but without neglecting the educational task of the members of the community, regardless of age and training. The pedagogical museum should be conceived as an educational institution open to the enjoyment of the whole community, and to its social, even economic, service. Beyond the cultural fashions and scientific or political conjunctures, and regardless of the pedagogical museum modalities that we can identify near us, attention should be paid to the social and community value of the patrimonial resource represented by a pedagogical museum.